Late Ancient Adornments on the Territory of Romania – a Means of Religious Propaganda at the Beginning of Christianity - Ioana-Iulia Olaru (Anastasis: Research in Medieval Culture and Art)
Though unjustly considered minor, miniature arts served political propaganda, bringing the Roman artistic concepts to the provinces of the Empire. In the late ancient period, the phenomenon of religious propaganda appeared, this propaganda was done by using these objects of reduced dimensions, the new ideology of Christianity in formation. Among these, adornments are one of the most ornamental pieces which record the triumphant path of the new religion, these luxury items are suitable means of promoting the new forms and the new symbolics.